2x^3-x^2+13x-6 factorize
Answers
Answer:
Step-by-step explanation:
2x³-x²+13x-6=0
2x³-x²+7x+6x-6=0
Hope it will help you with
Question :
2x³ - x² - 13x - 6
Solution:
2x³ - x² - 13x - 6
____________ [ GIVEN ]
• We have to solve it by factorization method
___________________________
=> 2x³ - x² - 13x - 6
Now.. we can write x² as x² - 2x². Because on solving we get - x².
Similarly 13x = - x - 12x
=> 2x³ + x² - 2x² - x - 12x - 6
Take commons
=> x²(2x + 1) -x(2x + 1) -6(2x + 1)
=> (x² - x - 6) (2x + 1)
Now.. x² - x - 6 is in the form ax² + bx + c
We have to find the numbers whose sum is 'b' and product is 'c'.
=> (2x + 1) (x² + 2x - 3x - 6)
=> (2x + 1) [x(x + 2) -3(x + 2)]
=> (2x + 1) (x - 3) (x + 2)
_____________________________
(2x + 1) (x - 3) (x + 2) are the factors
__________ [ ANSWER ]
_____________________________